The Misuse of Knowledge and Power in Mary Shelly’s Frankenstein (1818) - CHABIRA ,Hanane; CHERIF ,Ines; MOUISSA ,Fattoum (Faculty of Letters and Foreign Languages Department of English, 2019)
Knowledge and power have been studied in several literary works as a form of positive elements that take role in characters’ improvements and as constructive items that people should be attaining, they are typically perceived as elements that help in creating positive impact on people’s life. Both of the concepts are projected in Mary Shelly’s Frankenstein, or modern Prometheus. The following dissertation takes into consideration how the concepts of knowledge and power are manipulated and misused in the novel. This research examines how knowledge and power are related to each other by studying this relation through several characters. The main character, a scientist, represents how attaining powerful social status leads to the possibility of easier access to knowledge and how knowledge can be a mean on gaining power; furthermore, how knowledge is misused by defying natures rules. Similarly to knowledge, power and its projection is also explored by analysing the characters’ decisions, more precisely abusing power in a way that it is endangering to their life and the life of those among them